1999
DOI: 10.1046/j.1365-2141.1999.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of minimal residual disease in patients with BCR‐ABL‐positive acute lymphoblastic leukaemia using quantitative competitive polymerase chain reaction

Abstract: Summary. We analysed 20 patients with BCR-ABL-positive acute lymphoblastic leukaemia (ALL) by quantitative competitive polymerase chain reaction (QC-PCR) to study the kinetics of the leukaemic clone. Consecutive samples of 16 patients (minor-bcr, n 10; major-bcr, n 6) were analysed after conventional chemotherapy and/or bone marrow transplantation (BMT). DNA competitor templates co-amplifying with either p210 or p190 BCR-ABL cDNA were used for quanti®cation of leukaemia-speci®c BCR-ABL mRNA. In all samples, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 54 publications
4
32
0
2
Order By: Relevance
“…The second most frequent fusion transcript involves break points in a 5.8-kb region spanning exons 12-16, known as the major break-point cluster region (M-bcr) and is typical of chronic myeloid leukemia (CML) but is also seen in 30% of patients with Ph þ ALL. 34,36,37,56 Detection of BCR-ABL fusion transcripts by reverse transcription PCR is relevant not only for diagnostic purposes but also in particular for quantitative monitoring of MRD. 34 Several studies have shown that levels of MRD in the bone marrow (BM) of patients with Ph þ ALL, assessed by RQ-PCR after induction and after consolidation treatment, is a powerful indicator of prognosis.…”
Section: Pcr Analysis Of Bcr-abl Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most frequent fusion transcript involves break points in a 5.8-kb region spanning exons 12-16, known as the major break-point cluster region (M-bcr) and is typical of chronic myeloid leukemia (CML) but is also seen in 30% of patients with Ph þ ALL. 34,36,37,56 Detection of BCR-ABL fusion transcripts by reverse transcription PCR is relevant not only for diagnostic purposes but also in particular for quantitative monitoring of MRD. 34 Several studies have shown that levels of MRD in the bone marrow (BM) of patients with Ph þ ALL, assessed by RQ-PCR after induction and after consolidation treatment, is a powerful indicator of prognosis.…”
Section: Pcr Analysis Of Bcr-abl Transcriptsmentioning
confidence: 99%
“…Flow cytometric and molecular methods that allow sensitive detection and specific quantification of residual leukemic cells have been developed. [28][29][30][31][32][33][34][35][36][37][38][39][40] Standardization of methodologies and definitions of common MRD terms become increasingly important, not only to ensure comparability of MRD data between different MRD laboratories within a single MRD-based treatment protocol but also to provide a sound basis for the comparison of MRD results between different treatment protocols, including those that evaluate the effectiveness of new agents.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In one small study of five patients employing quantitative PCR, increases of 42 log in PB of two patients was closely followed by relapse while patients without such pronounced increase remained in CR for prolonged periods. 28 However, absolute quantitative parameters reflecting MRD levels and dynamics have not yet been established statistically to predict probability of relapse within a certain time period.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relatively low interassay variability has been found under specific experimental conditions, 28,31 the interassay variance may be substantially higher in the setting of a multicenter trial, in which sample shipment may impair RNA quality. Furthermore, the thresholds that were identified in our study need to be validated in future prospective trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation